Monitoramento audiológico em um grupo de crianças com indicadores de risco para a deficiência auditiva - Peixoto, Sabrina Alves Lima (2012)
Introduction: The audiologic monitoring of children with risk indicators for hearing loss (RIHL) aims at the early identification of hearing losses in order to provide adequate therapeutic intervention, and therefore to reduce its consequences upon speech and language development of such children. Aim: To study the results of the audiologic monitoring in a group of children with RIHL submitted to a two-stage protocol of neonatal hearing screening (NHS). Method: Sample was divided in two groups: group 1 (G1) failed transient otoacoustic emission (TOAE) and passed the second stage with Automated Brainstem Auditory Evoked Potential (A-BAEP); and group 2 (G2) with satisfactory results in both procedures, TOAE and A-BAEP. Data collecting included tympanometry, TOAE and Visual Reinforcement Audiometry (VRA) with insertion phones or in free field at 0.5, 1.0, 2.0 and 4.0 kHz. Children who could not be conditioned or who didn t allow the placement of insertion phones and/or bone transducer underwent click-BAEP or frequency specific BAEP at 0,5 and 2.0 KHz. Results: Of the 34 children submitted to audiologic monitoring, 9 presented conductive disorder 3 from G2 (N=17) and 6 from G1 (N=17). No sensorineural hearing losses were detected in both groups. Neonates with RIHL and who failed TOAE presented greater prevalence of conductive hearing disorders in the audiologic monitoring when compared to children who did not fail